The State's Right to Control (Droit De Regalie): The Regulatory Regime of Airspace and Outer Space in National Agrarian Law - Hendi Setiawan; Gita Ranjani; Graita Alfalaq Badnah (Simbur Cahaya, 2026)
This study examines the legal issue (juridical polemic) regarding the status of "outer space" in the Basic Agrarian Law (UUPA). The UUPA includes outer space as part of the national wealth under state control (HMN). However, this view has led to a conflict of norms after Indonesia ratified the 1967 Space Treaty through Law No. 16 of 2002. This international treaty affirms that outer space is the common heritage of humanity and prohibits any country from claiming sovereignty there. In addition, there is also the issue of the unclear vertical boundaries of "airspace", which is part of state sovereignty. This study aims to analyse the regulatory regime governing Airspace and Outer Space under the National Agrarian Law, and to identify the obstacles to implementing the State's Right of Control (HMN) over Outer Space following the enactment of the 1967 Space Treaty. The research method used is normative law, which focuses on the analysis of primary legal materials (such as the 1945 Constitution of the Republic of Indonesia, the Basic Agrarian Law, and Law No. 16/2002) and secondary legal materials. The results of the analysis show that there are two fundamentally different legal regimes. Airspace is treated as a territory of full and exclusive state sovereignty. However, this sovereignty has weaknesses, namely that it is not mentioned in the 1945 Constitution and is limited by the right of passage in the Indonesian Archipelagic Sea Lanes (ALKI). Conversely, outer space is entirely governed by international law, which prohibits sovereignty. The conclusion reached is that the State's Right of Control (HMN) over Outer Space cannot be exercised. This is due to two main obstacles: unresolved conflicts between the UUPA and the 1967 Space Treaty, and Indonesia's technological backwardness in utilising strategic resources in space, such as the Geostationary Orbit (GSO).